A curvature correction turbulent model for computations of cloud cavitating flows. Issue 1 (7th March 2016) - Zhao, Yu; Wang, Guoyu; Huang, Biao
Abstract : Purpose: – The purpose of this paper is to assess the predictive capability of the streamline curvature correction model (CCM) and investigate the unsteady vortex behavior of the cloud cavitating flows around a hydrofoil. Design/methodology/approach: – The design of the paper is based on introducing the curvature correction method to the original k-ε model. Calculations of unsteady cloud cavitating flows around a Clark-Y hydrofoil are performed using both the CCM and the baseline model. Findings: – Compared with the baseline model, better agreements are observed between the predictions of the CCM model and experimental data, especially the cavity shedding process. Based on the computations, it is demonstrated that streamline curvature correction of the CCM model can effectively decrease predicted turbulence kinetic energy and eddy viscosity in cavity shedding region. This leads to the better prediction for the recirculation zone located downstream of the attached cavity, and dynamics of this recirculation zone contribute to the formation and development of the re-entrant jet. Originality/value: – The authors apply streamline curvature correction to the calculations of unsteady cloud cavitating flows and discuss the interactions between the cavitation unsteadiness and vortex structures to get an insight of the correction mechanics.